The Dynamics of intercultural Conflict in Lecturer Performance Evaluation: The Perspective of Digital Immigrant Lecturers and Assessors (Study at Faculty of Social and Political Sciences of Universitas Tanjungpura Pontianak) - Wuysang, Julia Magdalena; Patriani, Ira; Rahmawati,; Pijoh, Feibe Engeline (Technium Social Sciences Journal, 2026)
This study examines the dynamics of intercultural conflict in communication during the lecturer workload performance evaluation (BKD) at the Faculty of Social and Political Sciences (FISIP), Tanjungpura University (UNTAN), Pontianak. It focuses on the differing perspectives between digital immigrant lecturers and assessors. The conflict arises from variations in technology usage, communication styles, and cultural norms between the two groups. The research addresses how cross-cultural communication conflicts impact the effectiveness of the performance evaluation process and how generational differences and technological experience shape perceptions and practices in evaluation. A qualitative research method was employed, involving in-depth interviews, thematic analysis, and theoretical analysis based on the Digital Natives vs. Digital Immigrants Theory (Prensky, 2001), Face Negotiation Theory (Ting-Toomey, 1985), Anxiety/Uncertainty Management Theory (Gudykunst, 2004), and Diffusion of Innovations Theory. The findings show that: 1) the mismatch in technological proficiency between assessors and lecturers is the primary cause of communication conflict; 2) tensions arising from face negotiation are heavily influenced by differences in communication styles and technology usage between assessors and digital immigrant lecturers, with the latter perceiving technology as a threat to their professional face; 3) the diffusion of innovation and differing perceptions of technology become the main sources of tension in the performance evaluation process; and 4) limited intercultural understanding is a key factor exacerbating conflicts in the evaluation process.